2002
DOI: 10.1007/s00167-002-0306-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of intraarticular application of tenoxicam, bupivacaine and tenoxicam: bupivacaine combination in arthroscopic knee surgery

Abstract: Arthroscopic knee surgery is one of the most common surgeries done in outpatient settings; however, postoperative pain is believed to be the major barrier for discharge and early rehabilitation. In this study we evaluated and compared the efficacy of intraarticular application of long-lasting non-steroidal analgesic drug tenoxicam, a long-lasting local anaesthetic bupivacaine and combination of the two on postoperative pain after arthroscopic knee surgery. With the approval of the local ethics committee and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 27 publications
1
36
0
4
Order By: Relevance
“…The third drug we administered is tenoxicam, a NSAID which has been used in studies intraarticularly, alone or in combination with local anaesthetics [8][9][10][11][12][13]. It has been shown that i.a tenoxicam provided superior postoperative analgesia and reduced analgesic requirements compared to intravenous tenoxicam indicating a peripheral analgesic effect [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…The third drug we administered is tenoxicam, a NSAID which has been used in studies intraarticularly, alone or in combination with local anaesthetics [8][9][10][11][12][13]. It has been shown that i.a tenoxicam provided superior postoperative analgesia and reduced analgesic requirements compared to intravenous tenoxicam indicating a peripheral analgesic effect [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…The use of intraarticular tenoxicam injection has been described for its long-lasting non-steroidal analgesic effect after arthroscopic knee surgery 30 , and because of its long half-life (60-80 h) local infiltration of the drug concentrates the pain-control effects in the local area 9 . Local infiltration of the drug also eliminates the systemic complications.…”
mentioning
confidence: 99%
“…The study is unique because there were few studies on post-operational pain thresholds in arthroscopic surgery, 10,11 and research on the topic concerning combination analgesics in arthroscopic surgery is still ongoing.…”
Section: Discussionmentioning
confidence: 99%